Studi Etnografi Virtual Pesan Nonverbal tentang Prinsip Menikah Muda dalam Instagram @nikahasik - Agus Setiaman, Siti Jauriah Atwar Bajari (Jurnal Komunikator, 2017)
This study aims to: Firstly, understand the relationships that occur in the use Instagram @nikahasik account by followers in understanding the concept of young married (early married). Secondly, explaining the verbal and nonverbal language that there were often used by followers @nikahasik in understanding the concept of young married.The research method used in this research was the virtual ethnography research. The data is generated through observation of some Instagram @nikahasik account followers who actively post comments, photos or images related to early marriage and matchmaking. Observations were conducted over a period of two months as well as on-line interviews with informants who were followers of Instagram @nikahasik.The results of the research show firstly, the users of the @nikahasik instagram account learn about various aspects of marriage through the account. Secondly, there are verbal and nonverbal languages used by Instagram @nikahasik followers on marital virtue rather than courtship, ceremony preparation of user account marriage until discussions about mating tips are supported with nonverbal messages to reinforce the impression displayed. The nonverbal messages used were emoticons trying to express a sense of fun, disappointment, sadness, compassion, and love.Â Keywords: @nikahasik, Instagram, young married, virtual ethnography, emoticonsÂ